The Latin continuation of William of Tyre - William, of Tyre, Archbishop of Tyre, approximately 1130-approximately 1190, author. Link
1 online resource.
Keywords: William of Tyre's monumental twelfth-century history of the First Crusade and the Latin Kingdom of Jerusalem inspired a rich series of interrelated Old French continuations that proved very popular in the later Middle Ages. In contrast to the thriving literary afterlife that William's work enjoyed in the vernacular, however, only one continuation of the text is known to have survived in Latin, the language in which William himself wrote. Completed in the early thirteenth century by an unknown ecclesiastical writer in England, this so-called Latin Continuation of William of Tyre picks up the threads of William's narrative soon after it breaks off in 1184 and goes on to provide a detailed account of the Muslimconquest of Jerusalemin 1187 and the subsequent Third Crusade. Drawing on a range of other written sources, the anonymous continuator of William's work nevertheless offers a unique contemporary perspective on the tumultuous events of the 1180s and early 1190s and on the crusaders' failure to recover Jerusalem. For the first time ever, this book provides a complete English translation of the Latin Continuation, together with a new critical edition of the text which, unlike the previous edition of 1934, incorporates both extant manuscripts. Written with both students and researchers in mind, the edition and translation are accompanied by a full critical apparatus, explanatory notes, and a detailed new discussion of the text in the introduction.